Impact of 68Ga-FAPI PET/CT on staging and oncologic management in a cohort of 226 patients with various cancers - Körber, Stefan A.; Röhrich, Manuel; Walkenbach, Leon; Liermann, Jakob; Choyke, Peter L.; Fink, Christoph Andreas; Schroeter, Cathrin; Spektor, Anna-Maria; Herfarth, Klaus; Walle, Thomas; Calais, Jeremie; Kauczor, Hans-Ulrich; et al. (Journal of nuclear medicine, 2023)
Since the development of fibroblast activation protein-targeted radiopharmaceuticals, 68Ga-fibroblast activation protein inhibitor (FAPI) PET/CT has been found to be suitable for detecting primary and metastatic lesions in many types of tumors. However, there is currently a lack of reliable data regarding the clinical impact of this family of probes. To address this gap, the present study aimed to analyze the clinical impact of 68Ga-FAPI PET/CT by examining a large cohort of patients with various tumors. Methods: In total, 226 patients (137 male and 89 female) were included in this retrospective analysis. Pancreatic cancer and head and neck cancers were the most common tumor types in this cohort. TNM stage and oncologic management were initially determined with gold standard imaging, and these results were compared with 68Ga-FAPI PET/CT. Changes were classified as major and minor. Results: For 42% of all patients, TNM stage was changed by 68Ga-FAPI PET/CT results. Most of these changes resulted in upstaging. A change in clinical management occurred in 117 of 226 patients. Although a major change in management occurred in only 12% of patients, there was a significant improvement in the ability to accurately plan radiation therapy. In general, the highest clinical impact of 68Ga-FAPI PET/CT imaging was found in patients with lung cancer, pancreatic cancer, and head and neck tumors. Conclusion: 68Ga-FAPI PET/CT is a promising imaging probe that has a significant impact on TNM stage and clinical management. 68Ga-FAPI PET/CT promises to be a crucial new technology that will improve on conventional radiologic imaging methods such as contrast-enhanced CT and contrast-enhanced MRI typically acquired for cancer staging.